2001
DOI: 10.1016/s0960-9822(01)00159-2
|View full text |Cite
|
Sign up to set email alerts
|

Opposing functions of Ki- and Ha-Ras genes in the regulation of redox signals

Abstract: Ras p21 signaling is involved in multiple aspects of growth, differentiation, and stress response [1-2]. There is evidence pointing to superoxides as relays of Ras signaling messages. Chemicals with antioxidant activity suppress Ras-induced DNA synthesis. The inhibition of Ras significantly reduces the production of superoxides by the NADPH-oxidase complex [3]. Kirsten and Harvey are nonallelic Ras cellular genes that share a high degree of structural and functional homology. The sequences of Ki- and Ha-Ras pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 23 publications
5
60
0
Order By: Relevance
“…17 We have found recently that the effects of Ha-Ras and Ki-Ras on ROS levels are complementary; Ha-Ras activates, and Ki-Ras reduces, intracellular ROS. 18,19 In the present study, we show that Ha-Ras protein increases the number of cells undergoing apoptosis after oxidative stress; conversely, the Ki-Ras isoform has a protective effect, encoded by a polybasic stretch of lysine residues at the COOH terminus of the molecule, not present in the Ha-Ras sequence.…”
supporting
confidence: 46%
See 4 more Smart Citations
“…17 We have found recently that the effects of Ha-Ras and Ki-Ras on ROS levels are complementary; Ha-Ras activates, and Ki-Ras reduces, intracellular ROS. 18,19 In the present study, we show that Ha-Ras protein increases the number of cells undergoing apoptosis after oxidative stress; conversely, the Ki-Ras isoform has a protective effect, encoded by a polybasic stretch of lysine residues at the COOH terminus of the molecule, not present in the Ha-Ras sequence.…”
supporting
confidence: 46%
“…We have recently found that Ki-Ras but not Ha-Ras stimulates the mitochondrial enzyme manganese superoxide dismutase (MnSOD) via ERK1/2 signaling and that the polybasic region of Ki-Ras is essential for this induction. 19 Taken together, the data suggest that Ki-Ras reduces H 2 O 2 -induced apoptosis by buffering the production of endogenous ROS via MnSOD-ERK1/2 signaling ( Figure 6). The difference between ERK1/2 activated by Ha-Ras or Ki-Ras is probably accounted for either by a different membrane compartmentalization 27,28 or by a discrete organelle localization encoded by the polybasic lysine stretch.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations